PENEMPATAN KARYAWAN BERDASARKAN ANALISIS JABATAN DAN ANALISIS BEBAN KERJA DINAS TANAMAN PANGAN, HORTIKULTURA DAN PERKEBUNAN PROVINSI SULAWESI SELATAN - Darsim, Sitti Khadijah Herdayani; Samandy, Annisa Aulliyah (ADMIT: Jurnal Administrasi Terapan, 2023)
This study was conducted so that t agencies can find out the qualification for each position and the number of employees needed, thus requiring a job analysis and workload analysis that must be made and updated in accordance with the regulations set out in Ministry of State Apparatus Utilization and Bureaucratic Reform Decree Number 1 of 2020. There were three informants in this study, using data collection techniques, namely interviews, observation, document review and documentation. Based on the results of the author's interview with the interviewees, the positions that will be interviewed directly by the author are several positions in the General, Personnel and Legal Subdivisions which will later be made a job analysis and workload analysis. Apparatus, Personnel Manager, Performance Analyst, and General Administration. The results of this study could reflect and interpret all the research results collected in a general and comprehensive manner so as to obtain a clear picture. Based on the calculation of job analysis and workload analysis that has been made, the position of the Head of the General, Personnel and Legal Sub section requires 1 person, the Personnel Manager position requires 6 people, the General Administration position requires 10 people, the Performance Analyst position requires 2 analysts and the Resource Analyst position Human Resources Apparatus requires 1 analyst.